Hubungan antara Perhatian Orang Tua dengan Motivasi Belajar Siswa - Ani Endriani (Universitas Pendidikan Mandalika, 2018)
Parents' attention, especially in terms of children's education, is needed. Moreover, what must be focused is the attention of parents on learning activities carried out by children daily in their capacity as students and knowledge claimants. The form of parental attention to children's learning can be in the form of providing guidance and advice, supervision of children's learning, providing motivation and appreciation and fulfilling children's learning needs. The purpose of this research was to determine the relationship between parental attention and learning motivation of class VIII students of SMPN 6 Praya Timur Lombk Tengah in the academic year 2015/2016. The population in this study were all students of class VIII SMPN 6 Praya Timur Lombok Tengah, amounting to 25 students, while the sampling technique used population techniques, namely 25 were all sampled, because they were less than 100.Data collection techniques used questionnaires, documentation, and analysis techniques. data using product moment correlation. The results showed that there was a relationship between parental attention and learning motivation in class VIII students of SMP Negeri 6 Praya Timur Lombok Tengah in the academic year 2015/2016, obtained based on data analysis using the correlation formula, the results obtained were r counted at 9.360, while the value of r table at the 5% significance level with N = 25 it is obtained 0.396. Thus, the calculated r value is greater than the r table value of 9.360> 0.396. The results of the research and data analysis indicate that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Therefore the results of this study are significant, so it can be concluded that this study is